Knowledge, attitude and practice related to diabetes mellitus in dentists of Nepal - Joshi, Bishal; Pokhrel, Buddhi Raj; Shrestha, Laxmi; Kar, Sanjit Kumar; Mahotra, Narayan Bahadur (Journal of Chitwan Medical College, 2022)
Background: Diabetes mellitus (DM) is one of the most common systemic diseases encountered by dentists in daily practice. The present study aimed to assess the knowledge, attitude, and practice of dentists regarding diabetes mellitus. Methods: This cross-sectional study was conducted among the dentists of Nepal from August to December 2020. A total of 345 dentists throughout the country took part in this study. A set of 27 self-designed questions was used as the study tool, among which 11 questions were about knowledge, seven were about attitude, and nine were about practice related to DM. The result was expressed in frequency and percentage. Chi square and Spearman’s correlation analysis were performed with SPSS version 16. Results: The mean knowledge score was 8.15 ± 1.54 with 11 being the highest possible score. Of the total participants, 252 (73%) had good knowledge regarding DM. The mean attitude score was 4.68 ±1.19, where seven was the highest possible score. Of the total respondents, only 190 (55.1%) had a positive attitude. The mean practice score was 7.19 ± 1.19, with nine being the highest possible score. A majority of the respondents (N = 320, 92.8%) had good practice habits regarding diabetic patients. Correlation analysis showed a weak positive but significant correlation among knowledge, attitude, and practice. Conclusions: There was good knowledge and practice in dentists though there were frequent areas of improvement in attitude. Various trainings like continuing medical educations (CME) may be beneficial to improve personal beliefs.